2016
DOI: 10.1007/s00586-016-4492-6
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the axial vertebral rotation measurements of adolescent idiopathic scoliosis using the center of lamina method on ultrasound images: in vitro and in vivo study

Abstract: The pilot study indicated the proposed COL method was a simple and reliable method to evaluate the AVR on ultrasound images. Standardization of the posture during ultrasound scan and taking radiograph is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Furthermore, different tools have been used to evaluate sagittal spinal curvature such as inclinometers ( Free-hand 3D ultrasound imaging, which combines a conventional B-mode imaging system with a position sensor, has been developed over two decades and recently become more popular due to its features of radiation-free, wider accessibility and lower cost in comparison with other 3D imaging modalities (Huang et al 2005 of the laminae method showed high intra-and inter-reliability and were comparable with those obtained from X-ray. Axial vertebral rotation obtained using the laminae method also showed high intra-and inter-reliability (Chen et al 2016), and good agreement was found between the laminae ultrasound results with those obtained by the Aaro-Dahlborn method in the magnetic resonance images (Wang et al 2016). Though there were various studies using ultrasound on the evaluation of vertebrae features, coronal spinal curvature and vertebrae rotation, no study has been reported on the reliability of 3D ultrasound imaging for evaluating the sagittal spinal curvature.…”
Section: )mentioning
confidence: 58%
“…Furthermore, different tools have been used to evaluate sagittal spinal curvature such as inclinometers ( Free-hand 3D ultrasound imaging, which combines a conventional B-mode imaging system with a position sensor, has been developed over two decades and recently become more popular due to its features of radiation-free, wider accessibility and lower cost in comparison with other 3D imaging modalities (Huang et al 2005 of the laminae method showed high intra-and inter-reliability and were comparable with those obtained from X-ray. Axial vertebral rotation obtained using the laminae method also showed high intra-and inter-reliability (Chen et al 2016), and good agreement was found between the laminae ultrasound results with those obtained by the Aaro-Dahlborn method in the magnetic resonance images (Wang et al 2016). Though there were various studies using ultrasound on the evaluation of vertebrae features, coronal spinal curvature and vertebrae rotation, no study has been reported on the reliability of 3D ultrasound imaging for evaluating the sagittal spinal curvature.…”
Section: )mentioning
confidence: 58%
“…These finding place this experimental model closer to morphological changes seen in human idiopathic scoliosis. Even the severity of the rotation at the apex of the primary curves (25.7° ± 16.3°) is within the range of vertebral rotation described in adolescent idiopathic scoliosis . Although in this model axial rotation is satisfactorily achieved, the intervention performed in these animals are not still parallel to the much subtler disturbances that can lead to a progressive rotatory deformity in human scoliosis.…”
Section: Discussionmentioning
confidence: 80%
“…They concluded that these deformities of AIS subjects vary with different positions, and the patterns of changes in sitting or sitting forward bending positions are highly subject dependent. Likewise, Chen et al 53 further investigated the intra-and interobserver reliability of axial vertebral rotation measurements of AIS subjects using the center of lamina method on 3D ultrasound images, and they found an intraclass correlation coefficient > 0.91 and mean absolute difference < 1.4 degrees. Several other studies used 3D ultrasound to assess scoliosis curves using different bony landmarks in either prone or supine positions.…”
Section: Three-dimensional Ultrasoundmentioning
confidence: 99%